PENGARUH KEPATUHAN, PEMERIKSAAN, DAN PENAGIHAN PAJAK PADA PENERIMAAN PAJAK PENGHASILAN BADAN - Mahendra, Putu Putra; Sukartha, I Made (E-Jurnal Akuntansi, 2014)
Each year the Director General of Taxation is required to always increase tax revenue, because in order to succeed in the construction sector tax revenue becomes very vital. Tax compliance, tax audits and tax collection are all factors that affect tax revenue. This study aims to determine the effect of tax compliance, tax audits and tax collection in corporate income tax revenue in the Tax Office (KPP) Primary Badung Utara. Populasi in this study were all effective corporate taxpayers registered in North Badung STO years 2009-2012. Source of data used are secondary data with multiple linear regression analysis as a technique of data analysis. Based on the results of analysis show that tax compliance, tax audits and tax collection has a positive effect on corporate income tax revenue in North Badung.
Keywords: compliance, audits, collection, tax revenue